2006
DOI: 10.1080/03098260500499709
|View full text |Cite
|
Sign up to set email alerts
|

Problem-based Learning in Geography: Towards a Critical Assessment of its Purposes, Benefits and Risks

Abstract: This paper makes a critical assessment of problem-based learning (PBL) in geography.It assesses what PBL is, in terms ofthe range of definitions in use and in light of its origins in specific disciplines such as medicine. It considers experiences of PBL from the standpoint of students, instructors and managers (e.g. deans), and asks how well suited this method of learning is for use in geography curricula, courses and assignments. It identifies some 'best practices in PBL', as well as some useful sources for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 31 publications
2
97
0
9
Order By: Relevance
“…A group presentation, the underlying rationales of this exercise were to encourage students to do independent inquiries and improve on their investigation and analytical skills through a case study format (Pawson et al, 2006;Yeung, 2010). Each group consisted of 4 or 5 members chose a past earthquake event and worked together in identifying the main queries they need to investigate on, considering the facts, opinions and ideas from a range of resources available online.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A group presentation, the underlying rationales of this exercise were to encourage students to do independent inquiries and improve on their investigation and analytical skills through a case study format (Pawson et al, 2006;Yeung, 2010). Each group consisted of 4 or 5 members chose a past earthquake event and worked together in identifying the main queries they need to investigate on, considering the facts, opinions and ideas from a range of resources available online.…”
Section: Methodsmentioning
confidence: 99%
“…The emphasis on critical thinking and problem solving is an attractive draw to tackle on the issue faced by most school students where they often fail to relate what they learned in classrooms to the world beyond the school walls (Rubin, 1996). Similar to the idea where medical students are required to analyse organs as a system in the human body, geography students need to be able to recognise the links between different aspects of the discipline, drawing insights on the concept and theories discussed previously and relate it to real world situations (Pawson et al, 2006). Concepts and theories can be discussed contextually in a systematic manner in classrooms through careful design of the problem case study for the students.…”
Section: Pbl In Geography Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fuller et al (2000) highlight that whilst the depth of understanding as a result of active learning techniques is difficult to assess objectively, it may accumulate over time with the consistent use of interactive methods. And in an assessment of problem-based learning among geography undergraduates, Spronken-Smith (2005, p. 214) found that students deemed this approach better than traditional lectures as it was 'hands-on, active and interactive', hence engendering an active learning experience (see also Burkhill, 1997 andPawson et al, 2006). Kolb's (1984) famous experiential learning cycle highlights the importance of active learning, or as Race (2002) refers to it, 'learning by doing'.…”
Section: Active Learningmentioning
confidence: 99%
“…She points out that problem-solving using authentic problems and scenarios seems to be the more sensible direction to take to prepare young professional teachers. Pawson et al (2006) confirm this and point out that '… there is little information available regarding the scope of use of PBL and PBL hybrids in Geography courses and curricula'. Only a few studies (Van LoggerenbergHattingh 2000;Golightly & Muniz 2013;Golightly & Raath 2015) could be found on the implementation and integration of PBL in existing teacher-training programmes within a South African context.…”
Section: Problem-based Learning and Geography Teacher Trainingmentioning
confidence: 63%